Use of epidermal cell suspension in burns wound management: A pilot study - Bharat Mishra; Vikas Singh; Chetna Arora (Wolters Kluwer Medknow Publications, 2020)
Introduction: It is a standard practice to cover the burn wounds with skin grafts at the earliest. Deficiency of donor skin seriously limits timely cover of extensive burns. Studies have shown that these autologous cells enhance the wound-healing process by reducing the time needed for the host cells to invade the wound tissue and by early synthesis of new skin this technique of enzymatically digesting small skin grafts, centrifuging the suspended cells and spraying the epidermal cells over burn raw areas may allow early healing. Aims and Objective: The aim of this study is to assess feasibility and role of epidermal cell suspension as wound cover in burns. Materials and Methods: This study was conducted at the burn center of a tertiary Hospital in India over a period of 1 year. Patients with postburn raw areas were included. Similar size two sites were identified in the patients. On one site cell suspension was applied, while other areas were managed with conventional dressings. Small piece of split-skin graft (SSG) was used to make cell suspension. Under anesthesia, required size of SSG was harvested from healthy donor site. Trypsinization of graft was done; epidermis was separated from the dermis. The epidermis was cut into tiny pieces, and patient's serum was added and centrifuged. Epidermal cell suspension was made, and viability of cells is confirmed using an inverted microscope. Meanwhile, the wound is thoroughly cleaned by soda bicarbonate solution. The freshly prepared keratinocytes suspension was applied on day 1, 3, and 5. Similar standard dressing protocol was followed on the control side. Wound assessment was done based on the percentage of reepithelization on the 7th and 14th day. Results: Twenty-eight patients (18 males and 10 females with a mean age of 34 years) were included the study. Cell suspension was sprayed on 4735 cm2 area. Wound size reduced to 2247 cm2 and 923 cm2 on the 10th and 14th day, respectively. While, at control site wound reduced to 3882 cm2 and 2134 cm2 on the 7th and 14th day, respectively. The difference in cell suspension and control treated area was found to be significant. Conclusion: Keratinocytes cell suspension is feasible in burns and improves the healing of wounds. However, larger studies are required to standardize and validate its use in major burns.